2012
DOI: 10.1039/c2jm34596j
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput roll-to-roll X-ray characterization of polymer solar cell active layers

Abstract: Synchrotron-based X-rays were used to probe active materials for polymer solar cells on flexible polyester foil. The active material was coated onto a flexible 130 micron thick polyester foil using rollto-roll differentially pumped slot-die coating and presented variation in composition, thickness, and additives. The coated foil was passed through a synchrotron X-ray beam on a small unit comprising unwinder and winder for the foil, an X-ray probe station, and a barcode reader for sample registration. Foil leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 25 publications
1
40
1
Order By: Relevance
“…[10][11][12][13][14][15][16] Second, X-ray diffraction shows that the crystallinity of P3HT increases from the unannealed to the annealed case. 5,12,[17][18][19] While X-ray diffraction has provided a useful comparison of pre and postannealing P3HT crystallinity, it is difficult to determine absolute crystallinity from this data, although a recent attempt at this has been accomplished.…”
mentioning
confidence: 98%
“…[10][11][12][13][14][15][16] Second, X-ray diffraction shows that the crystallinity of P3HT increases from the unannealed to the annealed case. 5,12,[17][18][19] While X-ray diffraction has provided a useful comparison of pre and postannealing P3HT crystallinity, it is difficult to determine absolute crystallinity from this data, although a recent attempt at this has been accomplished.…”
mentioning
confidence: 98%
“…As the performance of OFETs depends on the thin-film structures, various aspects and processing steps of conjugated oligomers and polymers have been studied by GIXRD including alignment [24], phase behavior [25,26], solution shearing [27], solvent vapour annealing [28], roll-to-roll processing [29], doctor-blading [30] and spray-processing in real time [31]. However, apart from the GIXRD studies of Liscio and co-workers [13] the GIXRD literature of OFETs in operando is less comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…9,20,21 The average lamellar packing distance for the untextured crystallites were a little larger(16.1 Å), contrary to earlier findings. 9 In the present study, the coated film was at all times kept at 70 • C, whereas the results reported by Böttiger et al 9 were obtained at room temperature. It may be speculated that untextured and textured crystallites exhibit different thermal expansion, but the exact mechanism for the difference is still being investigated, and underlines the need for further studies of the kinetics of roll-coated films.…”
Section: Resultsmentioning
confidence: 73%
“…Therefore this technique has been used extensively to study BHJ layers, both individually and as a part of fully functional solar cells, 6 but until now R2R processed solar cells have only been studied ex situ. 9 Few requirements for special sample environments enable in situ studies of materials, and at the same time the X-ray measurements give a statistical average over the whole thickness of the film, important especially in the case of BHJ films because their inner morphology is the most important factor to determine. P3HT crystallizes in various ways that have been reported in the litterature.…”
Section: Introductionmentioning
confidence: 99%